Metastatic spread of solid subtype lung adenocarcinoma to the small intestine with anemia and melena: A case report. Issue 34 (August 2017) - Ying, Xiaofang; Wang, Mingwei; Verma, Vivek; Wang, Manxiang; Ye, Shengwei; Bi, Jianping; Zhou, Xiaoyi; Han, Guang; Zhen, Weining
Abstract: Rationale: Metastasis to the small intestine from a primary lung cancer is rare, and is associated with a poor prognosis. Early diagnosis of small intestine metastasis is difficult because of the low incidence of clinically apparent symptoms. Patient concerns: Clinical data and treatment of a 59-year-old man with small intestine metastasis from primary solid subtype lung adenocarcinoma are summarized. Diagnoses: A man who was previously diagnosed with stage IIIA (T3N2M0) lung adenocarcinoma (solid subtype) came to our hospital for postoperative radiotherapy. Laboratory tests indicated anemia and melena. The patient was initially believed to have digestive ulcer and was treated with omeprazole, which proved to be ineffective. We conducted an abdominal computed tomography (CT) contrast scan and discovered a mass in the small intestine mass. Further positron emission tomography–computed tomography (PET-CT) imaging indicated the small intestine mass with fluorodeoxyglucose uptake. Interventions: The patient underwent an enterectomy and anastomosis. Pathological analysis confirmed the diagnosis of small intestinal metastasis from lung cancer with concomitant mesenteric lymph node metastasis. Outcomes: One month after the operation, hemoglobin levels became normal, and the patient had good quality of life. However, 3 months after the operation, the patient suffered from anemia again. An abdominal CT scan indicated a new small intestine mass. Progression continued rapidly, and the patient died of hemorrhagic shock 5.5 months after the resection of the small intestine mass. Lessons: Although uncommon, if lung cancer patients present with anemia and melena, enteric metastasis should be part of the differential diagnosis. Abdominal CT scans and PET-CT are effective for early diagnosis. The prognosis of metastatic spread of solid subtype lung adenocarcinoma to the small intestine with mesenteric lymph node metastasis is poor. Subgroups of patients benefitting from metastasectomy and more effective systemic therapy need to be further investigated.